2019
DOI: 10.12933/therya-19-787
|View full text |Cite
|
Sign up to set email alerts
|

A checklist of the parasitic helminths of cricetid and heteromyid rodents in Mexico

Abstract: We present an updated checklist of helminth species infecting cricetid and heteromyid rodents (Rodentia: Cricetidae and Heteromyidae) distributed in Mexico. For each helminth record, we include information on helminth taxonomy, location within the host, life stage, host associations, collection localities, citation, and museum collections, when available. We recorded more than 73 helminth species from 47 host species distributed across 21 states in Mexico. The present list represents the most up-to-date knowle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…In Mexico, metacestodes of Hyd. taeniaeformis have also been reported in the liver of cricetid and murid rodents (Preisser & Falcón-Ordaz 2019;Panti-May et al 2021). However, the length of large hooks of Hyd.…”
Section: Site Of Infection: Livermentioning
confidence: 98%
See 3 more Smart Citations
“…In Mexico, metacestodes of Hyd. taeniaeformis have also been reported in the liver of cricetid and murid rodents (Preisser & Falcón-Ordaz 2019;Panti-May et al 2021). However, the length of large hooks of Hyd.…”
Section: Site Of Infection: Livermentioning
confidence: 98%
“…Particularly, in Yucatan, only 11 helminth taxa have been recorded in 4 of 13 heteromyid and cricetid rodent species: 3 in H. gaumeri (Panti-May & Robles 2016;Panti-May et al 2018), 4 in P. yucatanicus (Panti-May et al 2018), 3 in Sigmodon toltecus (de Saussure) (Panti-May et al 2018) and 1 in Ototylomys phyllotis Merriam (Chitwood 1938). In Campeche and Quintana Roo, no helminths have been recorded in small rodents (Preisser & Falcón-Ordaz 2019). This clearly shows that the inventory of the helminths parasitizing wild small rodents is incomplete in the Yucatan Peninsula.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In Mexico, T. muris has been recorded mainly in commensal rodents such as M. musculus , R. rattus and Rattus norvegicus in the Mexican states of Hidalgo, Mexico City, Tabasco and Yucatan (Panti-May et al , 2021), with the only record from the wild rodent Heteromys irrotatus found in the state of Morelos (Preisser & Falcón-Ordaz, 2019). Meanwhile, in Argentina T. muris has only been recorded in R. rattus found in one city, Corrientes (Gómez Muñoz et al , 2018).…”
Section: Introductionmentioning
confidence: 99%